2010
DOI: 10.1111/j.1743-6109.2009.01587.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Exacerbates the Functional Deficiency of NO/cGMP Pathway Associated with Erectile Dysfunction in Human Corpus Cavernosum and Penile Arteries

Abstract: Introduction Diabetic men with erectile dysfunction (ED) are less responsive to therapy with type 5 phosphodiesterase (PDE5) inhibitors. Although an impairment of the nitric oxide (NO)/cyclic guanosin-monophosphate (cGMP) pathway has been shown in diabetic ED vs. non-diabetic ED, the functionality of NO/cGMP pathway in non-diabetic and diabetic ED patients with respect to non-ED patients has not been established. Aim The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
108
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 35 publications
8
108
0
8
Order By: Relevance
“…The efficacy of PDE5 inhibitors for treating ED is lower in diabetic patients (Vickers and Satyanarayana, 2002;El-Sakka, 2004). It has been recently demonstrated that capacity of sildenafil to relax HPRA is reduced in diabetic patients with ED (Angulo et al, 2010a). In addition to confirm the impaired vasodilatory capacity of sildenafil in HPRA from diabetic patients, the present results show that the activation of KCa with NS-8 potentiates the relaxant responses to PDE5 inhibition on HPRA from both diabetic and non-diabetic men.…”
Section: Figuresupporting
confidence: 68%
See 2 more Smart Citations
“…The efficacy of PDE5 inhibitors for treating ED is lower in diabetic patients (Vickers and Satyanarayana, 2002;El-Sakka, 2004). It has been recently demonstrated that capacity of sildenafil to relax HPRA is reduced in diabetic patients with ED (Angulo et al, 2010a). In addition to confirm the impaired vasodilatory capacity of sildenafil in HPRA from diabetic patients, the present results show that the activation of KCa with NS-8 potentiates the relaxant responses to PDE5 inhibition on HPRA from both diabetic and non-diabetic men.…”
Section: Figuresupporting
confidence: 68%
“…The ability of PDE5 inhibitors to relax isolated horse and human penile arteries and, rabbit and HCC, has been previously observed (Taher et al, 1997;Kalsi et al, 2004;Ruiz-Rubio et al, 2004;Angulo et al, 2010a). Relaxation of contracted HPRA and HCC caused by PDE5 inhibition is sensitive to blockade of NO synthesis or inhibition of soluble guanylyl cyclase, confirming the involvement of the NO/cGMP pathway in these responses.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The severity of endothelial dysfunction and peripheral neuropathy are mainly responsible for the poor responsiveness of diabetic patients to PDE5 inhibitors (8,9). Because the effects of PDE5 inhibitors depend on endogenous NO formation, PDE5 inhibitors fail to increase the cGMP level above the threshold required for penile erection if bioavailable NO is insufficient as the result of severe endothelial dysfunction or peripheral neuropathy (9). Therefore, a new treatment strategy that corrects both endothelial dysfunction and peripheral neuropathy is required for men with diabetic ED.…”
mentioning
confidence: 99%
“…The multiple factors causing diabetic ED contribute to reduced responsiveness to currently available oral phosphodiesterase-5 (PDE5) inhibitors, which enhance the nitric oxide (NO)-cGMP pathway by inhibiting the breakdown of cGMP (7). The severity of endothelial dysfunction and peripheral neuropathy are mainly responsible for the poor responsiveness of diabetic patients to PDE5 inhibitors (8,9). Because the effects of PDE5 inhibitors depend on endogenous NO formation, PDE5 inhibitors fail to increase the cGMP level above the threshold required for penile erection if bioavailable NO is insufficient as the result of severe endothelial dysfunction or peripheral neuropathy (9).…”
mentioning
confidence: 99%